Overcoming melanin interference in melanocyte photodynamic therapy with a pyrene-derived two-photon photosensitizer - Juvekar, Vinayak; Cao, Yu; Koh, Chang Woo; Lee, Dong Joon; Kwak, Sun Young; Kim, Sun Mi; Park, Tae Jun; Park, Sungnam; Liu, Zhihong; Kim, Hwan Myung (Chemical Engineering Journal, 2024)
Photodynamic therapy (PDT) is primarily applied in the treatment of skin diseases. However, conventional PDT is less effective for melanoma, a type of skin cancer that contains melanin pigment, due to melanin's broad absorption spectrum in the ultraviolet–visible region. This reduces the effectiveness of traditional photosensitizers (PSs) in PDT. Here, we introduced pyrene based two-photon (TP) PSs that are easy to synthesize. Among the π-extended pyrene derivatives, we have confirmed the synergetic generation of reactive oxygen species (ROS) with asymmetric pyrene (Py3). We proposed a mechanism explaining the higher ROS generation efficiency of Py3 compared with that of the symmetric derivatives through theoretical calculations. Py3 effectively stains the plasma membrane of melanoma cells and demonstrates superior PDT efficacy compared with Chlorin e6. As the melanin content increases in melanoma cells, cell death significantly decreases under visible light excitation; notably, it is minimally affected by TP irradiation at 750 nm. In 3D multicellular tumor spheroids with a high melanin content, Py3 showed high PDT efficacy through TP irradiation, whereas under visible light irradiation, PDT efficacy decreased. In experiments involving the injection of Py3 into the tail of mice with B16F10 and 4 T1 tumor models, followed by TP-PDT, we observed significant inhibition of tumor growth and high biocompatibility. Our results indicate a promising TP-PDT method for treating melanomas.
Keywords: Melanin content; Melanoma; Melanoma cells; Photon irradiation; Photosensitiser; Reactive oxygen species; Skin cancers; Skin disease; Two photon; Two-photon photodynamic therapies; Melanin; Melanoma; Photodynamic therapy; Photosensitiser; Pyrene; Two-photon